Presynaptic dysfunction caused by cerebrospinal fluid from a patient with the ataxic form of Hashimoto's encephalopathy. Issue 4 (25th July 2014) - Mitoma, Hiroshi; Yoneda, Makoto; Saitow, Fumihito; Suzuki, Hidenori; Matsunaga, Akiko; Ikawa, Masamichi; Mizusawa, Hidehiro
Abstract Background Hashimoto's encephalopathy is an autoimmune disease associated with Hashimoto's thyroiditis. The mechanism underlying the development of ataxia is unclear. Aim We examined whether impairment in synaptic transmission underlies the pathomechanism of Hashimoto's encephalopathy. Methods We tested the effects of cerebrospinal fluid from Hashimoto's encephalopathy patients on cerebellar synaptic transmission in rat cerebellar slices. The effects of cerebrospinal fluid from six patients with the ataxic form of Hashimoto's encephalopathy were examined using patch‐clamp recording in rat cerebellar slices. Results The cerebrospinal fluid of one patient, but not those of the other five patients, impaired presynaptic short‐term plasticity between parallel fiber‐Purkinje cell transmission in the cerebellum. The patient whose cerebrospinal fluid induced presynaptic impairment had hypothyroidism with a high titer of anti‐thyroid antibodies, and was positive for anti‐NH2‐terminal of α‐enolase antibodies in the cerebrospinal fluid. Conclusions These results suggest that defective glutamate release is a potential pathomechanism in some patients with Hashimoto's encephalopathy.